TITAN's digital RFQ ion beam cooler and buncher, operation and performance - Brunner, Thomas; Brodeur, Maxime; Gallant, Aaron; Simon, Vanessa Véronique (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
We present a description of the Radio Frequency Quadrupole (RFQ) ion trap built as part of the TITAN facility. It consists of a gas-filled, segmented, linear Paul trap and is the first stage of the TITAN setup with the purpose of cooling and bunching radioactive ion beams delivered from ISAC-TRIUMF. This is the first such device to be driven digitally, i.e., using a high voltage (Vpp=400V), wide bandwidth (0.2<f<1.2MHz) square-wave as compared to the typical sinusoidal wave form. Results from the commissioning of the device as well as systematic studies with stable and radioactive ions are presented including efficiency measurements with stable 133Cs and radioactive 124,126Cs. A novel and unique mode of operation of this device is also demonstrated where the cooled ion bunches are extracted in reverse mode, i.e., in the same direction as previously injected.
Gesehen am 27.09.2018